UTILIZATION OF REGIONAL GOVERNMENT ASSISTANCE IN INCREASING INCOME OF FISHERIES GROUP MEMBERS IN NAGARI MANGOPOH PALAK GADANG ULAKAN SUB DISTRICT ULAKAN TAPAKIS PADANG DISTRICT PARIAMAN - Suhur, Wirdas; Nugroho, Firman; Hendri, Ridar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study is about the use of local government assistance in increasing the income of members of fishermen groups carried out in August 2018 in the nanggari manggopoh palak gadang ulakan tapakis district padang pariaman district. This study aims to find out how members of the fishing group utilize local government assistance in increasing the income of members of the fishing group, hopefully. The method used in this study is a survey method that is analyzed using the simple T-test method and the number of respondents in this study, namely 19 respondents who were used using SPSS 16. From the results of this study the income of fishermen's catch increased by 75% after obtaining assistance, while the net income of fishermen increased by IDR. 1,500,000 per month. After the pairet simples test, the value of T count is -23,117, while the value of sig (2tailed) (0,000) <(0,05) can be concluded that rejecting H0 and accepting Hi means that there are differences before and after receiving assistance. Keywords:utilization of assistance, regional government